Membrane-targeting antibacterial isoniazid schiff base against S. aureus and biofilms - Liu, Yaguang; Hu, Lianzhi; Liu, Binbin; Qu, Zheng (Frontiers in Chemistry, 2025)
IntroductionBuilding upon previous research, this study focuses on the replication and evaluation of a series of hydrazone derivatives derived from isoniazid.MethodsThe lead compound, identified as C5, was assessed for its antibacterial activity against Gram-positive bacteria, notably Staphylococcus aureus ATCC 29213. Its hemolytic potential, cytotoxicity (against VERO cells), and ability to induce resistance were evaluated. Mechanistic studies included assays for membrane depolarization (using DiSC35 fluorescence), membrane integrity (via SYTOX Green uptake), measurement of intracellular ATP levels, and detection of reactive oxygen species (ROS). Additional investigations examined its effect on LPS-induced NO/TNF-α release in macrophages and its activity against S. aureus biofilms.ResultsCompound C5 exhibited potent antibacterial activity (MIC = 16 μg/mL against S. aureus ATCC 29213). It demonstrated no hemolysis and low cytotoxicity (IC50 > 128 μg/mL). A time-kill assay achieved complete eradication of S. aureus within 16 hours at 8× MIC, and the compound showed a low tendency to induce resistance. The mechanistic studies revealed that C5 disrupts the bacterial membrane, causing depolarization, loss of integrity, and leakage of proteins/DNA. It also induced ROS accumulation and significantly reduced ATP levels. Furthermore, C5 suppressed LPS-induced NO/TNF-α release in macrophages (p < 0.01) and inhibited/disrupted S. aureus biofilms.DiscussionThese results demonstrate that C5 possesses a multifunctional mechanism of action, combining direct bactericidal activity through membrane targeting with anti-biofilm efficacy and immunomodulatory properties. This multifaceted profile highlights its strong potential as a promising candidate for combating resistant bacterial infections.